Proceedings of the Workshop on Non-Photorealistic Animation and Rendering 2014
DOI: 10.1145/2630397.2630406
|View full text |Cite
|
Sign up to set email alerts
|

Stylized keyframe animation of fluid simulations

Abstract: simulation 45 keyframe 50 in-between 53 in-between 57 keyframe 60 in-between 65 keyframe 70Figure 1: An upward-flowing jet of ink rendered in oil pastel. An underlying simulation is used as input to guide the artwork (frame 45 is shown). Frames 50, 60 and 70 are hand-drawn keyframes, while the remaining in-betweens were generated automatically by our system. AbstractWe present a method that combines hand-drawn artwork with fluid simulations to produce animated fluids in the visual style of the artwork. Given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…[ Kwatra et al 2005] [Bénard et al 2013] [Browning et al 2014] our approach Figure 13: Results and comparison (see text for details): a single frame (No. 135) extracted from a longer sequence synthesized using [Kwatra et al 2005], [Bénard et al 2013], [Browning et al 2014], and our approach on five different exemplars of fluid elements (shown in the bottom right corner in each view).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ Kwatra et al 2005] [Bénard et al 2013] [Browning et al 2014] our approach Figure 13: Results and comparison (see text for details): a single frame (No. 135) extracted from a longer sequence synthesized using [Kwatra et al 2005], [Bénard et al 2013], [Browning et al 2014], and our approach on five different exemplars of fluid elements (shown in the bottom right corner in each view).…”
Section: Resultsmentioning
confidence: 99%
“…They were recently applied to stylization of fluid simulations [Browning et al 2014] with compelling results. Nevertheless, a key drawback is that the user must prepare a set of keyframes that roughly match the appearance of the target flow at selected time steps.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some early works explored these ideas for synthesizing 2D textures directly on 3D fluids [89,90]. More recently, patch-based fluid synthesis research has focused on stylizing and synthesizing fluid flows that match a target exemplar [91][92][93]. Ma et al [91] focused on synthesizing high-resolution motion fields that match an exemplar, while the low-resolution flow matches a simulation or other guidance field.…”
Section: Synthesis For Specialized Domainsmentioning
confidence: 99%
“…Ma et al [91] focused on synthesizing high-resolution motion fields that match an exemplar, while the low-resolution flow matches a simulation or other guidance field. Browning et al [92] synthesized stylized 2D fluid animations that match an artist's 16 Synthesis for 3D fabrication. Left: results from Martínez et al [87].…”
Section: Synthesis For Specialized Domainsmentioning
confidence: 99%